2023
DOI: 10.1002/sstr.202300091
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Defective Nanosheet Subunit ZnIn2S4 Hollow Nanoflowers for Efficient Photocatalytic Hydrogen Evolution

Shuoping Ding,
Igor Medic,
Norbert Steinfeldt
et al.

Abstract: Constructing hierarchical and ultrathin‐structured metal sulfides is beneficial for achieving high‐efficiency hydrogen evolution catalysts. Herein, ZnIn2S4 (ZIS) hollow nanoflowers (HNFs) composed of ultrathin nanosheets are creatively synthesized via a facile trisodium citrate‐mediated and stirring‐assisted solvothermal method. Experimental results reveal that the synergy effect of ethanol, trisodium citrate, and continuous stirring during solvothermal synthesis process play a significant role in optimizing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Specific morphologies can also be obtained by leveraging the coordination effect of solvents. In a study conducted by Ding et al, [85] a structure-directing agent, trisodium citrate, was added to a solvent mixture of ethanol and water to promote the formation of hollow ZnIn 2 S 4 structures with introduced S vacancies. The authors detected the presence of coordination interactions between the citrate groups and metal ions via Fouriertransform infrared spectroscopy analysis.…”
Section: Pretreatment-based Defect Preparation and Applicationsmentioning
confidence: 99%
“…Specific morphologies can also be obtained by leveraging the coordination effect of solvents. In a study conducted by Ding et al, [85] a structure-directing agent, trisodium citrate, was added to a solvent mixture of ethanol and water to promote the formation of hollow ZnIn 2 S 4 structures with introduced S vacancies. The authors detected the presence of coordination interactions between the citrate groups and metal ions via Fouriertransform infrared spectroscopy analysis.…”
Section: Pretreatment-based Defect Preparation and Applicationsmentioning
confidence: 99%
“…19 In particular, ZnIn 2 S 4 (ZIS) is a promising candidate for O 2 photoactivation due to its tunable band gap (2.06-2.85 eV), exceptional chemical stability, and low toxicity. [20][21][22] Previous studies have shown that the initial step in O 2 photoactivation involves the adsorption of O 2 onto ZIS, followed by electron transfer from ZIS to O 2 , resulting in the generation of ROS. 23 However, the capability of ZIS to activate O 2 and transfer surface charge is limited.…”
Section: Introductionmentioning
confidence: 99%